Representasi Sikap Sabar dalam Novel Cinta Laki-Laki Biasa Karya Asma Nadia - Erlina Zahar; Sujoko Sujoko (Universitas Batanghari Jambi, 2020)
This study aims to describe the representation of patience value in the novel Cinta Laki-laki Biasa by Asma Nadia. This type of research is literary research, which is descriptive qualitative. The research data was taken from the novel Cinta Laki-laki Biasa by Asma Nadia, namely words, sentences, and paragraphs that express quotations representing patient attitudes. The data source of this research is the novel Cinta Laki-laki Biasa by Asma Nadia. The data collection technique in this research is to use the documentation carried out to analyze the contents of a novel, especially the representation of patience value in the novel Cinta Laki-laki Biasa by Asma Nadia. The results showed that the representation of patience in accepting various trials in the novel Cinta Laki-laki Biasa by Asma Nadia contained 26 quotes.